ANALYSIS OF STUDENTS’ DECISION MAKING TO SOLVE SCIENCE REASONING TEST OF TRENDS IN INTERNATIONAL MATHEMATICS AND SCIENCE STUDY (TIMSS) - Novianawati, N.; -, Nahadi (Jurnal Pendidikan IPA Indonesia, 2015)
This study aims to determine students’ decision making strategy to answer TIMSS science reasoning test in cognitive reasoning domain. This research is quantitative descriptive research. The result shows that students tend to use compensatory strategy for decision making in solving multiple-choice questions and use rational category to answer essay questions. The result shows that more than half of students have been able to answer the questions TIMSS science tests correctly.